THE EXPERIENCE OF THE CLIMACTERIC PERIOD FOR WOMEN WITHOUT CHILDREN - Mazzetto, Fernanda Moerbeck Cardoso; Marin, Maria José Sanches; Ferreira, Maria de Lourdes da Silva Marques [UNESP]; Orso, Livia Faria (Instituto Politecnico de Viseu, 2019)
Introduction: The climacteric period is a phase of modifications in the ovarian function that presents psychic, endocrine and somatic changes. This phase has been the subject of few studies and it has been the target of several taboos for many years. Objectives: To understand the climacteric experience of women without children. Methods: Exploratory descriptive study with a qualitative approach. Ten women, without children, attended in the basic health network were interviewed. The analysis of data was based on the Thematic Analysis. Results: The following themes were developed based on the analysis: Feelings for not being mothers, Reasons for non-maternity and Forms of compensation. Conclusions: The knowledge on the climacteric experience of women without children made it possible to recognize and understand the feelings of frustration, impotence and failure for not being mothers. Family abandonment, loneliness, stigmatization, and the reduction of social interaction are present manifestations. However, there are those women that opt for non-maternity, privileging autonomy, professional life and maternal instinct. To compensate, they replace the absence of children with dedication to nephews, students and pets.
LA VIVENCIA DEL CLIMATERIO PARA MUJERES SIN HIJOS
A VIVÊNCIA DO CLIMATÉRIO PARA MULHERES SEM FILHOS
Keywords: Climacteric period; Femininity; Gender identity; Infertility; Women’s health